Evaluación de consentimiento de alimento balanceado sobre el crecimiento de la especie endémica Trichomycterus dispar (mauri) viable para la acuicultura - Amaru Chambilla, Glicerio R. (2024)
The aim of this study was to contribute with methodologies to recover mauri (Trichomycterus dispar) populations and to the diversification of aquaculture in the Puno, Peru region. In total, 300 mauri specimens were used from the artificial reproduction of Villa Santiago – Pomata, in Puno, Peru. A culture system was conditioned and the acceptance of microsphere balanced food for the mauri was evaluated from the larval stage to 60 days of culture. Likewise, the growth of the fish was determined for 365 days. The incubation and obtaining of fingerlings were carried out at the facilities of the Peruvian Sea Institute (IMARPE), Puno headquarters. During stomach dissection at 45 days, less than 50% pellets were observed in the stomach contents; however, after 60 days, this percentage increased to more than 50%, even reaching 100%. This occurred when the fish had an average size and weight of 2.14 cm and 0.061 g, respectively. This stage was considered the beginning of the use of balanced food. At the end of the study (365 days) the mauri had an average size and weight of 4.87 cm and 0.712 g, respectively. The specific growth rate (SGR) was between 0.83 and 1.5, while the feed conversion factor was between 1 to 1.5. The study shows that the species has potential for cultivation in an intensive system, as well as for repopulation in the juvenile stage.